Charge Scheduling of an Energy Storage System under Time-of-Use Pricing and a Demand Charge - Yoon, Yourim; Kim, Yong-Hyuk (TheScientificWorld, 2014)
A real-coded genetic algorithm is used to schedule the charging of an energy storage system (ESS), operated in tandem with renewable power by an electricity consumer who is subject to time-of-use pricing and a demand charge. Simulations based on load and generation profiles of typical residential customers show that an ESS scheduled by our algorithmcan reduce electricity costs by approximately 17%, compared to a system without an ESS and by 8% compared to a scheduling algorithm based on net power.